Jin Worship, Founders’ Cults, and Social Relations in Tidore, Indonesia - Seung-Won Song (Religions, 2021)
This article examines perceptions of jin rituals in Tidore in order to explore how Austronesian perceptions of founders’ cults, arrival-order precedence, and stranger-kingship operate in determining social relations. Tidore origin narratives are significant historical texts that encode the social order and its power relations and so must be explored in greater depth. I analyzed rituals, origin narratives, and public discourse through interviews conducted with locals and particularly with four sowohi, the ritual specialists of jin worship. Additionally, I observed the public aspects of the jin ritual of inauguration of the sultan. The jin are the ancestral spirits and “true owners” of Tidore. Both the jin and sowohi are associated with the land and thus are the autochthonous leaders on the island. The sultan belongs to the stranger-king category, which was formed by later immigrant groups. During jin rituals of worship, the jin bless the sultan through the sowohi, who serve as mediums; this symbolizes the autochthonous flow of blessings to later immigrant groups. The rituals are also a recollection of a more primordial social order of heterogenous groups, which is based on the arrival-order precedence on Tidore.